Eksplorasi Penggunaan Teknik WRAP (Writing Assistance via Prompting) dalam Meningkatkan Keterampilan Menulis - Mauliska, Nur; Husnah, Rif'atul; Amalia Sholehah, Clarisya (Kalam Nusantara Institute, 2024)
This study aims to explore the use of WRAP (Writing Assistance via Prompting) technique in improving writing skills among university students. The WRAP technique, which utilizes the help of writing prompts to facilitate the writing process, has been identified as a potential tool to effectively improve writing skills. This research used a qualitative approach with a case study method to understand university students' experiences and perceptions of this technique. Data were collected through in-depth interviews, observations, and analysis of participants' writing documents. The results showed that the WRAP technique can improve students' creativity, confidence, and writing structure. Participants reported improved abilities in organizing ideas and overcoming writer's block. In addition, the technique also facilitated constructive feedback, allowing students to develop writing skills iteratively. The findings suggest that the integration of the WRAP technique in the writing curriculum can provide significant benefits to the development of students' academic writing skills. This study concludes that the use of the WRAP technique as a pedagogical tool needs to be further considered to support writing learning at the higher education level.